Literasi Investasi Untuk Komunitas Perempuan Di Bojonegoro - Handayani, Anita (JURNAL PENGABDIAN MANAJEMEN, 2025)
The aim of service activities is to provide literacy about investment. The investment literacy referred to in this service is investment literacy in the capital market, namely stock investment. This stock investment was introduced to the women's community (housewives) to provide an overview of the importance of investment and the implementation of stock investment. This investment literacy was carried out in the women's community (housewives) in Trojalu Village, Baureno District, Kab. Bojonegoro. This service activity is carried out in two stages, namely the literacy stage by providing literacy on the importance of investment, and the next stage, namely the implementation of investing in shares through one of the securities companies, which was chosen because it does not require large costs because the costs are quite affordable, namely only One hundred thousand rupiah